2018
DOI: 10.1002/jlb.5a1117-462rr
|View full text |Cite
|
Sign up to set email alerts
|

NK cell recruitment in salivary glands provides early viral control but is dispensable for tertiary lymphoid structure formation

Abstract: Salivary glands (SGs) represent a permissive site for several sialotropic viruses whose persistence is linked to the development of autoimmunity. Natural Killer (NK) cells play a key role in viral clearance but their involvement in viral infection control and in tertiary lymphoid structures (TLS) development within SGs is unknown. By using an inducible model of TLS in the SGs of wild‐type C57BL/6 mice, induced by the local delivery of a replication‐defective adenovirus (AdV), we demonstrated that circulating N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 41 publications
(103 reference statements)
0
9
0
Order By: Relevance
“…To investigate the control of SG inflammation by IL‐27, we utilized a well‐established model of inducible sialadenitis, characterized by an early activation of the resident stroma and innate immune cells, followed by accumulation of T cells and B cells, and the formation of ELS with functional GCs (Supplementary Figure 3A, http://onlinelibrary.wiley.com/doi/10.1002/art.41289/abstract).…”
Section: Resultsmentioning
confidence: 99%
“…To investigate the control of SG inflammation by IL‐27, we utilized a well‐established model of inducible sialadenitis, characterized by an early activation of the resident stroma and innate immune cells, followed by accumulation of T cells and B cells, and the formation of ELS with functional GCs (Supplementary Figure 3A, http://onlinelibrary.wiley.com/doi/10.1002/art.41289/abstract).…”
Section: Resultsmentioning
confidence: 99%
“…Here, CD4 + T cells are high producers of this cytokine throughout the time course. Importantly and shown previously, NK cells are also key producers of granzyme-B and IFN-γ within the SG at early time points after viral infection (between 3 and 10 dpc) (27). We therefore hypothesise that while NK cells greatly decrease in number by 10 dpc ( 27), T cells expand and take over the production of these effector molecules.…”
Section: Functional Phenotype Of Infiltrating T Cellsmentioning
confidence: 53%
“…Finally, inducible models utilise Ro, M3R or other antigens to immunise mice leading to autoantibody production and impaired SG function (23,24). Recently, we demonstrated that a virusinduced murine model of SG inflammation and ELS formation developed in our laboratory (25), can be used to study the role of key players in ELN (25)(26)(27)(28). This model recapitulates some of the characteristics of SS, including periductal lymphoid aggregates, ELS and breach of self-tolerance within 19 days of viral infection (25).…”
Section: Introductionmentioning
confidence: 95%
“…Since both bacterial and viral agents have been implicated in the pathogenesis of periodontal disease [44][45][46][47], it is likely that suboptimal induction of IFN-γ will have profound effects on the clearance of both types of organism and the resolution of inflammation [48][49][50]. Therefore, the increase in the numbers and activation of NK cells in periodontal infection may have a direct relationship to the increase in colonization with the viral and bacterial infections since NK cells are the primary effectors that mediate lysis of virally infected cells.…”
Section: Discussionmentioning
confidence: 99%